Study On Cardiovascular Disease Classification Using Machine Learning Approaches (International Journal of Engineering and Computer Science, 2015)
The diagnosis of heart disease which depends in most cases on complex grouping of clinical and pathological data. Due to this complexity, the interest increased in a significant amount between the researchers and clinical professionals about the efficient and accurate heart disease prediction. In case of heart disease, the correct diagnosis in early stage is important as time is very crucial. Numeral number of tests must be requisite from the patient for detecting a disease. Machine learning based method is used to classify between healthy people and people with disease. Cardiovascular disease is the principal source of deaths widespread and the prediction of Heart Disease is significant at an untimely phase. In order to reduce number of deaths from heart diseases there has to be a quick and efficient detection technique. This work presents a comprehensive review for the prediction of cardiovascular disease by using machine learning based approaches.